Abundance, diversity and foraging behavior of the flower-visiting insects of mango in Gazipur, Bangladesh - Md Zahid Hasan; Md Ramiz Uddin Miah; Md Moshiul Islam; Mansura Afroz; Suh, Sang Jae; Md Ruhul Amin (Penerbit Universiti Kebangsaan Malaysia, 2025)
To investigate the abundance, diversity, and diurnal dynamics of insect visitors associated with mango flowers, the present study was conducted in a mango orchard of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh from June 2020 to August 2021. The observed insect visitors represented 13 families of four taxonomic orders: Hymenoptera, Diptera, Lepidoptera, and Coleoptera. Hymenoptera showed the highest abundance (47.2%), with ants being the most abundant species (21.2±3.5/30 sweeps), followed by honeybees (11.2±0.9/30 sweeps). Furthermore, Hymenopteran insects showed the highest diversity (H’= 2.85), richness (Dmg= 0.56), and dominance (DBP=0.27) among the four orders. Epilachna beetles had the highest foraging speed (27.8±2.4 s/flower), followed by blister beetles (27.1±1.9 s/flower). Blow flies showed the lowest foraging speed (16.5±1.3 s/flower) but the highest visitation frequency (13.7±0.9 flowers/min). The abundance of ants, honeybees, and blowflies showed significant positive correlations with visitation frequency (0.905, 0.972, and 0.926, respectively) but a significant negative correlation with foraging speed (−0.968, −0.933, and −0.931, respectively). The diurnal pattern of insect visitors showed that the highest foraging activities occurred in the first part of the day (7.00 to 11.00 h) and then declined, with the lowest activity at 15.00 h.